Hepatocellular carcinoma on cirrhosis complicated with tumoral thrombi extended to the right atrium: results in three cases treated with major hepatectomy and thrombectomy under hypothermic cardiocirculatory arrest and literature review. Issue 1 (December 2016) - Pesi, Benedetta; Giudici, Francesco; Moraldi, Luca; Montesi, Gianfranco; Romagnoli, Stefano; Pinelli, Fulvio; Stefano, Pierluigi; Batignani, Giacomo
Abstract Background Hepatocellular carcinoma (HCC) with the presence of tumor thrombus in hepatic veins and vena cava, until the atrium (RATT), is correlated with poor prognosis and with risk of tricuspid valve occlusion, congestive heart failure, and pulmonary embolism. Methods Three patients with HCC on cirrhotic liver with RATT were studied. Operative technique, pre-operative and post-operative liver function tests, blood loss and transfusions, post-operative morbidity and mortality, and the overall survival and the disease free survival were analyzed. Results Mean operative time was 336 ± 66 min. Intra-operative blood loss was 926.6 ± 325.9 ml. No major complications occurred. The times of hospital stay were 10, 21, and 19 days, respectively. The survival times were 90, 161, and 40 days, and the disease-free survival times were 30, 141, and 30 days, respectively. Conclusions The complete removal of HCC with RATT may be achieved with cardiopulmonary by-pass (CPB) and total hepatic vascular exclusion (THVE). Adding the hypothermic cardiocirculatory arrest (HCCA) to the use of CPB allowed us to have minimal blood loss and hemostasis of the resectional plane. So the use of CPB and HCCA should be considered a good therapeutic alternative to the normothermic CPB with THVE.